Prevalence of comorbidity in primary care patients with type 2 diabetes and its association with elevated HbA1c: A cross-sectional study in Croatia. (2nd January 2016) - Bralić Lang, Valerija; Bergman Marković, Biserka
Abstract: Objective To the authors' knowledge, there are few valid data that describe the prevalence of comorbidity in type 2 diabetes mellitus (T2DM) patients seen in family practice. This study aimed to investigate the prevalence of comorbidities and their association with elevated (≥ 7.0%) haemoglobin A1c (HbA1c) using a large sample of T2DM patients from primary care practices.Design A cross-sectional study in which multivariate logistic regression was applied to explore the association of comorbidities with elevated HbA1c.Setting Primary care practices in Croatia.Subjects Altogether, 10 264 patients with diabetes in 449 practices.Main outcome measures Comorbidities and elevated HbA1c.Results In total 7979 (77.7%) participants had comorbidity. The mean number of comorbidities was 1.6 (SD 1.28). Diseases of the circulatory system were the most common (7157, 69.7%), followed by endocrine and metabolic diseases (3093, 30.1%), and diseases of the musculoskeletal system and connective tissue (1437, 14.0%). After adjustment for age and sex, the number of comorbidities was significantly associated with HbA1c. The higher the number of comorbidities, the lower the HbA1c. The prevalence of physicians' inertia was statistically significantly and negatively associated with the number of comorbidities (Mann–Whitney U test, Z = –12.34; p < 0.001; r = –0.12).Conclusion There is a high prevalence of comorbidity among T2DM patients in primary care. A negative association of number of comorbidities and HbA1c is probably moderated by physicians' inertia in treatment of T2DM strictly according to guidelines. Key points: There is a high prevalence of comorbidity among T2DM patients in primary care. Patients with breast cancer, obese patients, and those with dyslipidaemia and ischaemic heart disease were more likely to have increased HbA1c. The higher the number of comorbidities, the lower the HbA1c.